Effects of low-carbohydrate diet therapy in overweight subjects with autoimmune thyroiditis: possible synergism with ChREBP - Esposito, Teresa (Drug Des Devel Ther, 2016)
The thyroid is one of the metabolism regulating glands. Its function is to determine the amount of calories that the body has to burn to maintain normal weight. Thyroiditides are inflammatory processes that mainly result in autoimmune diseases. We have conducted the present study in order to have a clear picture of both autoimmune status and the control of body weight. We have evaluated the amount of either thyroid hormones, or antithyroid, or anti-microsomal, or anti-peroxidase antibodies (Abs) in patients with high amounts of Abs. In a diet devoid of carbohydrates (bread, pasta, fruit, and rice), free from goitrogenic food, and based on body mass index, the distribution of body mass and intracellular and extracellular water conducted for 3 weeks gives the following results: patients treated as above showed a significant reduction of antithyroid (−40%, P<0.013), anti-microsomal (−57%, P<0.003), and anti-peroxidase (−44%, P<0,029) Abs. Untreated patients had a significant increase in antithyroid (+9%, P<0.017) and anti-microsomal (+30%, P<0.028) Abs. Even the level of anti-peroxidase Abs increased without reaching statistical significance (+16%, P>0064). With regard to the body parameters measured in patients who followed this diet, reduction in body weight (−5%, P<0.000) and body mass index (−4%, P<0.000) were observed. Since 83% of patients with high levels of autoantibodies are breath test positive to lactase with a lactase deficit higher than 50%, this fact led us to hypothesize a correlation with carbohydrate-responsive element-binding protein and therefore a possible role of carbohydrate metabolism in the development and maintenance of autoimmune thyroiditis associated with body weight increase and slower basic metabolism.